Clinical analysis of microscopic modified ostium obstruction surgery for symptomatic sacral Tarlov cysts - HUANG Qin‐guo; WU Yan‐yu; LI Hong; ZHOU Qiang; PENG Lin; LU Yun‐tao (Chinese Journal of Contemporary Neurology and Neurosurgery)
Background Microsurgical techniques are increasingly being recommended for the treatment of symptomatic Tarlov cysts (TCs) due to improved long⁃term outcomes compared to those of other strategies. However, these techniques are associated with a high risk of cysts recurrence and cerebrospinal fluid (CSF) leakage, resulting in the surgical strategy of TCs remains controversial. We hypothesize that incomplete closure of the ostium between the cysts and the subarachnoid space is the probable cause of surgical failure. Accordingly, we present a novel method of cysts separation and ostium closure that aims to block the ostium more firmly and reliably. Methods Thirty ⁃ five consecutive patients underwent the microscopic modified ostium obstruction surgery in Nanfang Hospital, Southern Medical University due to symptomatic sacral TCs from January 2016 to March 2021. The operation time, intraoperative blood loss, postoperative hospitalization time, follow⁃up time, as well as the situation of nerve roots passing through the cysts and the postoperative outcome of the cysts were recorded. Visual Analogue Scale (VAS) was used before surgery, at discharge and at the last follow ⁃up, and Scoring System for the Clinical Evaluation of Patients with Spinal Processes (SCPS), Oswestry Disability Index (ODI), Japanese Orthopedic Association Scores (JOA29) and MacNab criteria were used before surgery and at the last follow ⁃ up to evaluate neurological function. Postoperative complications (infection, nerve injury, CSF leakage, postoperative adhesion, etc.) were recorded, and the cysts recurrence was observed by follow⁃up MRI. Results A total of 74 cysts were detected in 35 patients, among which 49 (66.26%) were large cysts (diameter > 1.50 cm), and cysts mainly compressed S1 nerve roots (22 cysts, 29.73%) and S2 nerve roots (36 cysts, 48.65%), all of which had fistulas and nerve roots passing through them. Average follow⁃up was (37.78 ± 17.19) months. To the last follow⁃up, the most significant symptom improvement rate was nerve root pain (94.29%, 33/35), followed by perineal pain (13/14), lumbosacral pain (85.19%, 23/27), orthostatic headache (2/3), neurogenic claudication (5/8), lower limb numbness (12/20), perineal numbness (7/14), sexual dysfunction (4/9), bowel dysfunction (8/19) and bladder dysfunction (6/17). The nerve root pain score (P = 0.000, 0.000), lumbosacral pain score (P = 0.000, 0.001) and perineal pain score (P = 0.001, 0.009) at the last follow⁃up were lower than those before surgery and at discharge, while those at discharge were lower than those before surgery (P = 0.000, 0.000, 0.001). The total score of SCPS (P = 0.000), pain and sensory disturbance (P = 0.000), muscle strength (P = 0.000), gait (P = 0.000) and urinal function (P = 0.019) at the last follow⁃up were higher than those before surgery. ODI index (P = 0.000) and pain level (P = 0.000), lifting/carrying (P = 0.000), walking (P = 0.000), sitting (P = 0.000), standing (P = 0.000), sleeping (P = 0.000), personal care (P = 0.000), social activities (P = 0.000) and travel (P = 0.000) at the last follow⁃up were lower than those before surgery. The overall improvement rate of both JOA29 and MacNab criteria was 94.29% (33/35). After surgery, 2 patients had new symptoms of lower limb numbness, and none had recurrence of cysts or CSF leakage. Conclusions The microscopic modified ostium obstruction surgery is a safe and effective strategy for management of patients with symptomatic sacral TCs, and is associated with a low incidence of cysts recurrence and CSF leakage since it achieves complete closure of cysts ostium.